Effects of presenteeism on productivity of government employees in Putrajaya: A regression analysis approach / Mastura Mohamad ...[et al.] - Mohamad, Mastura; Hasan, Hazlin; Syed Wahid, Sharifah Norhuda; Suhaimi, Muhamad Hafiz (Universiti Teknologi MARA Cawangan Pahang, 2021)
Presenteeism is a situation when an employee insists on going to work with an unhealthy body despite requiring prompt rest. It has become a worldwide phenomenon and linked to the loss of productivity among employees more so than absenteeism. Productivity of the public sector is very important as it has a huge impact on the economic performance of a country. Thus, it is imperative to study the effect of presenteeism, focusing on personal factors and organizational policies dimensions, on the productivity of government employees in Putrajaya. The regression analysis approach using IBM-SPSS AMOS 24 software was used to determine the effect of presenteeism on productivity of government employees. A total of 108 respondents were selected using stratified sampling technique and answered a set of questionnaires. The study found a moderate positive relationship between personal factors and productivity (r = 0.57, p < 0.01) and weak positive relationship (r = 0.390, p < 0.01) between organizational policies and productivity. The dimension of personal factors was identified as a significant positive predictor towards productivity (β = 0.53, p = .000) which indicated that the greater the personal factors are, the more positively motivated the employees would be toward their job productivity. The study concluded that a better understanding on issues of presenteeism by the management would provide some insights on how the government agencies could assist the employees in dealing with the problems, thus enabling them to give better and efficient services to the public.